2018
DOI: 10.7554/elife.38970
|View full text |Cite
|
Sign up to set email alerts
|

Epitope resurfacing on dengue virus-like particle vaccine preparation to induce broad neutralizing antibody

Abstract: Dengue fever is caused by four different serotypes of dengue virus (DENV) which is the leading cause of worldwide arboviral diseases in humans. Virus-like particles (VLPs) containing flavivirus prM/E proteins have been demonstrated to be a potential vaccine candidate; however, the structure of dengue VLP is poorly understood. Herein VLP derived from DENV serotype-2 were engineered becoming highly matured (mD2VLP) and showed variable size distribution with diameter of ~31 nm forming the major population under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 74 publications
(116 reference statements)
0
34
0
Order By: Relevance
“…The maturity of flavivirus VLPs affects epitope display and antigenicity. The 6B6C-1 Mab of the conformational-dependent Mabs performs the specific ability to bind mature flavivirus VLPs [55]. In dot blot analysis ( Figure 3) and MAC-ELISA assays (Figure 5), the specific binding of JEV human sera and two conformation-sensitive mAbs (6B6C and D56-3) to VLPs demonstrated that the secreted JEV VLPs maintained virion-like epitopes with maturity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The maturity of flavivirus VLPs affects epitope display and antigenicity. The 6B6C-1 Mab of the conformational-dependent Mabs performs the specific ability to bind mature flavivirus VLPs [55]. In dot blot analysis ( Figure 3) and MAC-ELISA assays (Figure 5), the specific binding of JEV human sera and two conformation-sensitive mAbs (6B6C and D56-3) to VLPs demonstrated that the secreted JEV VLPs maintained virion-like epitopes with maturity.…”
Section: Discussionmentioning
confidence: 97%
“…The process of flavivirus maturation is regulated by the proteolytic cleavage of the precursor membrane protein (prM) [54]. The maturity of VLPs affects the display and antigenicity of epitopes [55]. The conformationally dependent Mab 6B6C-1 specifically binds mature flavivirus VLPs, such that dot blot analysis results obtained using 6B6C-1 Mab ( Figures 3A and 4A) indicated that the JEV VLPs were mature.…”
Section: Discussionmentioning
confidence: 99%
“…77 More recently, a study demonstrated that a highly mature DENV-2 strain 16681-derived virus-like particles (mD2VLP) produced from mammalian COS-1 cells can generate higher cross-reactive NtAbs, and mice receiving passively transferred antibodies from immunized mice were protected against all four serotypes of DENV. 32 Further, cryo-EM reconstruction showed that these mD2VLP particles possess a T = 1 icosahedral symmetry with a groove located within the E protein dimers near the 2-fold vertices and exposed highly overlapping, cryptic neutralizing epitopes. 32 The results highlighted the potential of these "epitoperesurfaced" mature-form D2VLPs in inducing quaternary structure-recognizing broadly cross-reactive NtAbs.…”
Section: Current Dengue Vaccine Candidates Developed With Consideratimentioning
confidence: 97%
“…32 Further, cryo-EM reconstruction showed that these mD2VLP particles possess a T = 1 icosahedral symmetry with a groove located within the E protein dimers near the 2-fold vertices and exposed highly overlapping, cryptic neutralizing epitopes. 32 The results highlighted the potential of these "epitoperesurfaced" mature-form D2VLPs in inducing quaternary structure-recognizing broadly cross-reactive NtAbs. Covalently locked E protein dimers through cross-linking of the inter-subunit disulfide bonds is another dengue vaccine design that can also present resurfaced conformational EDE epitopes and with reduced exposure of the immunodominant FLE.…”
Section: Current Dengue Vaccine Candidates Developed With Consideratimentioning
confidence: 97%
See 1 more Smart Citation